PERAN PENDIDIKAN JASMANI DALAM MENGEMBANGKAN KETERAMPILAN SOSIAL DAN EMOSIONAL SISWA SEKOLAH DASAR - Tri Wahyu Ristiyanto; Rias Fitria; Cucu Atikah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to identify the role of physical education in developing social and emotional skills among elementary school students. Utilizing a qualitative approach, this research gathers data through literature review methods by analyzing relevant literature and previous studies. Social and emotional skills are essential aspects of child development that contribute to academic success and social competence. As an integral part of the elementary school curriculum, physical education provides opportunities for students to learn cooperation, communication, and emotion management through various physical activities and games. The results of the study indicate that physical education effectively enhances students' social skills, such as teamwork, communication, and tolerance, through team activities that require interaction and active participation. Additionally, physical education helps students manage their emotions, especially when facing wins and losses in games. These findings align with Vygotsky's social development theory, which emphasizes the importance of social interaction in child development, as well as Goleman's emotional intelligence theory, which highlights self-regulation and emotional management. The implications of this research demonstrate that physical education serves not only as a medium for physical skill training but also as an effective means to holistically develop students' social and emotional skills. Therefore, strengthening physical education in the elementary school curriculum is expected to help shape better character and personality in students. This study recommends that physical education be designed with a greater emphasis on developing students' social and emotional aspects to contribute to their overall development.